Nanostructured lipid carriers with liquid crystal structure encapsulating phenylethyl resorcinol: Characterization and in vitro study. (2nd July 2016) - Jia, F.; Gao, H.; Jia, H.; Zhang, W.
ABSTRACT: A new nanocarrier encapsulation technology that combined the advantages of liquid crystal (LC) and nanostructured lipid carriers was developed to overcome the problems related to the presence of phenylethyl resorcinol (PR) in cosmetic products. This paper described the characterization and in vitro evaluation of nanostructured lipid carriers (NLC) with an LC structure encapsulating PR (PR–LC–NLC). It demonstrated a spherical morphology, high drug entrapment efficiency, and excellent long-term stability. A prolonged release profile of PR from PR–LC–NLC was obtained. And it increased the PR's skin retention in the in vitro penetration study.